Avaliação da dependência com a pressão de propriedades estruturais de compostos orgânicos de interesse farmacêutico - Castro, Rosane de Paula (2018)
This thesis presents the structure determination using single crystal x-ray crystallography of four drug candidates under ambient conditions of temperature and pressure, as well as submitted to high pressure. The crystallographic analysis of this type of compound allows to obtain the three-dimensional structure in an unambiguous way. This information is useful for the development process of new drugs in order to achieve the planned properties, such as the study of combinations of the drug with the excipients to be used to guarantee the rate of expected release of the drug in the human body and the optimization of interaction between the drug and the target. Furthermore during the process of drug manufacturing in the pharmaceutical industry polymorphic phases may arise due to the application of pressure, which occurs during grinding and in the preparation of tablets, which may alter the bioavailability, solubility and stability of the medicament. Thus, identifying the conditions under which such modifications may occur guarantees the reliability of the final product. In this sense, the crystallization and crystallographic analysis of drug candidates developed by the Laboratório de Avaliação e Síntese de Substâncias Bioativas (LASSBio) of the Universidade Federal do Rio de Janeiro (UFRJ) was carried out. The compounds analyzed were: LASSBio-1773 and LASSBio-1774, which have hypoglycemic activity, LASSBio-1606, with anti-inflammatory properties, and LASSBio-1735, which has been shown to be active against several types of cancer. For the compounds LASSBio-1774 and LASSBio-1606 X-ray diffraction at high pressures was also performed with Diamond Anvil Cell (DAC), determining their unit cells and analyzing the effects of pressure on the crystalline arrangement. In both compounds reversible phase transitions were observed. The analysis of the structural changes for LASSBio-1774 due to pressure was performed with the aid of strain tensors.